Girl falling : a novel [large type] - Scrivenor, Hayley (Thorndike Press large print mystery series., 2025)
"The USA Today bestselling, Lambda Award-winning author of Dirt Creek is back with a woman's story of the aftermath of the climbing incident that killed her girlfriend--and getting to the truth. Torn between her girlfriend, Magdu, and her best friend, Daphne, Finn is looking forward to a day of rock climbing and bonding for the three women on the soaring cliffs near their Australian town. But nothing goes as she planned, and in a horrific accident, Magdu falls to her death. Rocked by grief, Finn tries to pinpoint where it all went wrong. Did Magdu die because of Finn's friendship with overbearing Daphne, who has never wanted Finn to change or leave her? Can Finn trace it all the way back to the tragic childhood loss of her sister? What about Magdu's family, who would never have accepted their relationship? When the police suspect foul play in Magdu's death, Finn begins to search for the shocking truth about her relationships and what has been in front of her all along. Beautifully written by the #1 internationally bestselling, Lammy Award-winning Hayley Scrivenor, Girl Falling is a beautiful love story, a tender meditation on grief, and a searing tale of just how much our lies can cost us"--